An Evaluation of the Thermophysical Properties of Stoichiometric CeO2 in Comparison to UO2 and PuO2. Issue 11 (7th August 2014) - Nelson, Andrew T.; Rittman, Dylan R.; White, Joshua T.; Dunwoody, John T.; Kato, Masato; McClellan, Kenneth J.; White, A. M.
<x xml:space="preserve">Abstract</x> The thermal conductivity of stoichiometric CeO2 was determined through measurement of thermal expansion from 313 to 1723 K, thermal diffusivity from 298 to 1473 K, and specific heat capacity from 313 to 1373 K. The thermal conductivity was then calculated as the product of the density, thermal diffusivity, and specific heat capacity. The thermal conductivity was found to obey an (A + BT)−1 relationship with A = 6.776×10−2 m·K·W−1 and B = 2.793 × 10−4 m·W−1. Extrapolations of applied models were made to provide suggested data for the specific heat capacity, thermal diffusivity, and thermal conductivity data up to 1723 K. Results of thermal expansion and heat capacity measurements agreed well with the limited low‐temperature data available in the literature. The thermal conductivity values provided in the current study are significantly higher than the only high‐temperature data located for CeO2. This is attributed to the tendency of CeO2 to rapidly reduce at elevated temperatures given the available partial pressure of O2 in air at ambient pressure. The CeO2 data are compared to literature values for UO2 and PuO2 to evaluate its suitability as a surrogate in nuclear fuel systems where thermal transport is a primary criterion for performance